The fibrinolytic potential of proteolytic enzymes on plasma microclots: a comparative analysis of long COVID patients using fluorescence microscopy and imaging flow cytometry - Usher, Thomas James (Stellenbosch : Stellenbosch University, 2025)
Usher, Thomas James. 2024. The fibrinolytic potential of proteolytic enzymes on plasma microclots: a comparative analysis of long COVID patients using fluorescence microscopy and imaging flow cytometry. Unpublished masters dissertation. Stellenbosch : Stellenbosch University [online]. Available: https://scholar.sun.ac.za/handle/10019.1/131941